Transcutaneous electrical acupoint stimulation (TEAS) treatment improves pregnancy rate and implantation rate in patients with implantation failure - Ya-Chiung Hsu; I-Ting Liang; Shang-Yu Huang; Hsin-Shih Wang; Yung-Kuei Soong; Chia-Lin Chang (Elsevier, 2017)
Objective: Although major advances have greatly improved the outcomes of assisted reproductive technology in the last two cascades, there remains significant difficulty in achieving pregnancy for many patients even after repeated attempts of IVF. Interestingly, recent studies have shown that transcutaneous electrical acupoint stimulation (TEAS) can improve the reproductive outcomes of select IVF patients. To determine the utility of TEAS in improving IVF outcomes in patients with a history of implantation failure, we conducted a retrospective study of clinical outcomes of women, who had a prior history of unsuccessful pregnancy outcome after IVF-embryo transfer (IVF-ET), following TEAS treatment. Materials and methods: A total of 25 patients, who had failed to conceive after multiple IVF cycles in which good embryos were transferred, received noninvasive low frequency TEAS treatment prior to and during an IVF-ET cycle. The clinical outcomes, including biochemical pregnancy rate, clinical pregnancy rate and implantation rate, were compared to those of prior cycles which received only standard IVF treatment. Results: Analysis of reproductive outcomes showed that implantation rate and clinical pregnancy rate increased significantly in IVF cycles that included the TEAS treatment when compared to prior cycles that received only the standard IVF treatment in this cohort of patients. Conclusions: This surprising finding indicated that TEAS treatment is a promising technique to improve reproductive outcomes in difficult cases of IVF-ET. Because TEAS treatment is noninvasive and has high reproducibility, and can be applied with limited training, further refinement of this procedure would not only substantiate the beneficial effects of TEAS, but also allow the technique to be more effective and reproducible.